Optimization of the operating conditions of azeotropic distillation columns with pervaporation membranes - Hoch, Patricia Monica (2003)
The main objective of this work is the optimization of the operating conditions of azeotropic distillation columns in hybrid distillation/pervaporation systems. In the configuration analyzed, a liquid side stream extracted from the azeotropic distillation column with the distributing non-key component is treated in a pervaporation membrane while the retentate is recycled to the column. The pervaporation membrane separates the pure distributing non-key component from the mixture, thus helping to improve the purity in the top and/or bottom products of the distillation column. The case study shows the hybrid process of a distillation column combined with pervaporation membranes, compared to the classical two-column process for Methyl tert-Butyl Ether production. In both cases, the operating conditions of the distillation columns such as reflux ratio, product and side draw flowrates are selected optimally. The numerical results show a significant reduction in operating cost obtained by using a pervaporation membrane instead of the second column in the original process.